The Hypnobirth Relaxation Influences Anxiety, Labor Pain, and APGAR Score in Newborns - Rosalinna, Rosalinna; Kurniarum, Ari; Puspita Sari, Luthfiana (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2024)
Introduction: Hypnotherapy has been developed to improve labor outcomes. However, research on the effects of anxiety, pain and APGAR measured simultaneously is still rarely carried out. This study evaluated the effect of hypnobirthing relaxation techniques on anxiety, labor pain, and APGAR scores of newborn babies. Methods: This study used a Quasy experiment. This study used two groups: control and treatment. The control group received no intervention, while the treatment group was given hypnobirthing. Anxiety and pain levels were measured with standard scales, and APGAR scores were assessed within the first minute. Results: The results showed that the control group experienced an increase in anxiety from 33.4 (SD=4.1) to 34.5 (SD=3.5) and pain of 5.83 (SD=1.7). The treatment group experienced a decrease in anxiety from 28.0 (SD=3.8) to 26.7 (SD=3.7), pain decreased to 3.57 (SD=1.7), and the APGAR score increased to 8.3 (SD=0.5). Statistical analysis showed significant differences (ρ < 0.0001).). Conclusion: Hypnobirthing effectively reduces anxiety, labor pain and improves APGAR scores. Therefore, midwifery care for mothers can include hypnobirthing techniques that can be integrated by health supervisors in preparation for childbirth. Latar Belakang: Hypnotherapy telah dikembangkan untuk meningkatkan luaran persalinan. Namun demikian, efek penelitian pada kecemasan, nyeri dan APGAR yang diukur bersamaan masih jarang dlakukan. Penelitian ini mengevaluasi efek teknik relaksasi hypnobirthing terhadap kecemasan, nyeri persalinan, dan skor APGAR bayi baru lahir. Metode: Penelitian ini menggunakan Quasy experiment Studi ini menggunakan dua kelompok: kontrol dan perlakuan. Kelompok kontrol tidak menerima intervensi, sementara kelompok perlakuan diberikan hypnobirthing. Tingkat kecemasan dan nyeri diukur dengan skala standar, dan skor APGAR dinilai pada satu menit pertama. Hasil: Hasil menunjukkan kelompok kontrol mengalami peningkatan kecemasan dari 33,4 (SD=4,1) menjadi 34,5 (SD=3,5) dan nyeri sebesar 5,83 (SD=1,7). Kelompok perlakuan mengalami penurunan kecemasan dari 28,0 (SD=3,8) menjadi 26,7 (SD=3,7), nyeri berkurang menjadi 3,57 (SD=1,7), dan skor APGAR meningkat menjadi 8,3 (SD=0,5). Analisis statistik menunjukkan perbedaan signifikan (ρ < 0,0001). Simpulan: Hypnobirthing efektif mengurangi kecemasan, nyeri persalinan dan meningkatkan skor APGAR. Oleh karena itu, Asuhan kebidanan pada ibu dapat memasukkan teknik hypnobirthing dapat diintegrasikan oleh Penyelia kesehatan dalam persiapan persalinan.